Prevalence and Characteristics of Staphylococcus aureus Associated with Meat and Meat Products in African Countries: A Review - Thembeka Thwala; Evelyn Madoroba; Albert Basson; Patrick Butaye (Antibiotics, 2021)
Antimicrobial resistance has been increasing globally, which negatively affects food safety, veterinary, and human medicine. Ineffective antibiotics may cause treatment failure, which results in prolonged hospitalisation, increased mortality, and consequently, increased health care costs. Staphylococcus aureus causes a diverse range of infections including septicaemia and endocarditis. However, in food, it mainly causes food poisoning by the production of enterotoxins. With the discovery of methicillin-resistant S. aureus strains that have a separate reservoir in livestock animals, which were termed as livestock-associated methicillin-resistant S. aureus (LA-MRSA) in 2005, it became clear that animals may pose another health risk. Though LA-MRSA is mainly transferred by direct contact, food transmission cannot be excluded. While the current strains are not very pathogenic, mitigation is advisable, as they may acquire new virulence genes, becoming more pathogenic, and may transfer their resistance genes. Control of LA-MRSA poses significant problems, and only Norway has an active mitigation strategy. There is limited information about LA-MRSA, MRSA in general, and other S. aureus infections from African countries. In this review, we discuss the prevalence and characteristics of antimicrobial susceptible and resistant S. aureus (with a focus on MRSA) from meat and meat products in African countries and compare it to the situation in the rest of the world.